The Role of the Government Internal Control Apparatus (APIP) and Corruption Control Strategy in Increasing Regional Original Revenue (PAD) in Indonesia - Zainuddin Zainuddin; Andi Chairil Furqan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Regional Original Revenue (PAD) plays a vital role in ensuring regional fiscal independence, yet many local governments in Indonesia still rely heavily on central transfers. This study aims to analyze the role of the Government Internal Control Apparatus (APIP) and corruption control strategies in improving PAD, as well as to identify the most affected PAD components. Using a quantitative research method with local government data from 2022 and a total of 534 observations at the provincial, regency, and city levels, this study employs simple linear regression analysis. The findings reveal that the role of APIP and effective corruption control strategies significantly and positively affect the increase of PAD. Specifically, regional taxes and other legitimate local revenues show consistent improvement, while regional levies and segregated regional wealth management exhibit insignificant influence from the tested variables. These results underscore the importance of strengthening APIP’s supervisory function and implementing integrated anti-corruption measures to enhance accountability and optimize regional revenue management. The study concludes that effective internal control and corruption prevention are essential for fiscal independence, and recommends future research using multi-year panel data and moderation variables for deeper analysis.